Response of seed germination and seedling growth of Physalis accession from East Java. (June 2020) - Mastuti, R; Waluyo, B; Batoro, J
Abstract: Environmental conditions significantly affects response of seed germination. This study aims to determine ex vitro and in vitro seed germination capacity and seedling growth of accession of Physalis sp derived from East Java including Madura Island. Ex vitro germination was carried out in mixed soil media: compost: husk charcoal while in vitro germination was carried out in agar-solidified medium. Ex vitro germinated seeds are generally able to produce 80-100% seedling in all accessions. Accessions from Madura Island have a better growth response compared to accessions from East part of Java Island. Although in vitro germination response was lower, the four accessions from the island of Madura namely A1 (Sumenep), A2 (Sampang), A4 (Sampang) and A5 (Pamekasan) have been able to produce regeneration and multiplication of shoots in vitro. The potential for in vitro growth in Physalis accessions needs to be developed to supply germplasm as a source of natural products in a controlled environment.